2012
DOI: 10.1007/s10853-012-6360-z
|View full text |Cite
|
Sign up to set email alerts
|

Strain-rate dependence of the tensile strength of glass fibers

Abstract: It is well known that the strength of glass fibers increases with increasing strain rate. Consequently, impact strength of glass fiber is competitive with that of carbon fiber. This strengthening phenomenon is well recognized for bulk glass. Strain-rate dependence of the strength for bulk glass was described by considering slow crack growth in glass. The analytical model that considered the slow crack growth of glass is proposed to predict the strength of glass fibers. The proposed model considered the stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 22 publications
2
19
0
Order By: Relevance
“…A similar observation by utilizing a tension split Hopkinson pressure bar and a high-speed tensile-testing machine over the strain rate from 8.33 × 10 −4 to 500 s −1 was reported by Taniguchi et al. 28,29 They observed that by increasing the strain rate from the quasi-static condition to 50 s −1 , the ultimate strength increased significantly; while beyond this strain rate, the increasing rate was declined. Nevertheless, the increasing ratio of the strength from the quasi-static condition to the strain rate of 250 s −1 is about 60%.…”
Section: Introductionsupporting
confidence: 77%
See 3 more Smart Citations
“…A similar observation by utilizing a tension split Hopkinson pressure bar and a high-speed tensile-testing machine over the strain rate from 8.33 × 10 −4 to 500 s −1 was reported by Taniguchi et al. 28,29 They observed that by increasing the strain rate from the quasi-static condition to 50 s −1 , the ultimate strength increased significantly; while beyond this strain rate, the increasing rate was declined. Nevertheless, the increasing ratio of the strength from the quasi-static condition to the strain rate of 250 s −1 is about 60%.…”
Section: Introductionsupporting
confidence: 77%
“…By having material constants (ψ and ξ) and Young's modulus ( E ), the mechanical behavior of glass fibers at different strain rates can be predicted. However, experimental data 2629 showed that Young's modulus of glass fibers is a rate-dependent parameter and increased by increasing the strain rate. To account for the rate dependency, equation (4) needs some modifications to include a strain rate-dependent elastic modulus instead of a constant one.…”
Section: The Strain-rate Dependent Mechanical Properties Of Glass Fibersmentioning
confidence: 99%
See 2 more Smart Citations
“…Using fibre bundles for testing can solve this problem to some extent but usually leads to another problem, friction between the fibres (Arao, Taniguchi, Nishiwaki, Hirayama, & Kawada, 2012). Typically the diameter of a fibre is in the range of 5e10 mm, making it very difficult to apply a true axial cyclic stress to a single fibre.…”
Section: Reliable Data On Fatigue Of Fibres: a Challengementioning
confidence: 99%